Thermo-Mechanical Stability and Gas-Tightness of Glass-Ceramics Joints for SOFC in the System MgO-BaO/SrO-B2O3-SiO2 - Rodríguez-López, Sonia; Malzbender, Jürgen; Justo, Virginia M.; Serbena, Francisco C.; Groß-Barsnick, Sonja M.; Pascual, Maria J. (Frontiers in Materials, 2020)
The objective of this paper is to illustrate a variety of studies carried out to improve the quality of some particular glass-ceramic joining materials for SOFC based on measured properties such as gas-tightness and mechanical resistance. First, the sealing conditions have been optimized for the two selected compositions in the system MgO-BaO/SrO-B2O3-SiO2. Once the joining materials have been optimized, the gas-tightness has been measured as a function of the glass-ceramic crystallization degree, its thermal cycling behaviour and the influence of a reducing atmosphere on this property. The electrical resistance at high temperature has also been studied. Subsequently, the chemical compatibility of the joints steel/glass-ceramic has been evaluated by means of the analysis of the cross-sections using SEM and EDX. Furthermore, the stability of the joints has also been studied as a function of the crystallization degree, the resistance versus thermal cycling and the influence of a reducing atmosphere. Finally, the mechanical resistance of the joints regarding flexural loading has been characterized employing a 4-point bending method at room temperature and at relevant high temperatures varying the seal thickness. Overall, the results verify that the developed and tested materials are promising for long term stable SOFC and SOEC application in advanced stack designs aiding prolonged lifetime under thermal-cyclic conditions.